Aproximación al comportamiento del flujo de efectivo con Dinámica de Sistemas - Carreño Dueñas, Diego Andrés; Salazar Sanabria, Hugo Felipe; Mesa Mojica, Josué Iván (Ingeniería, 2022)
Context: Cash flow is an essential element for decision-making within organizations, since knowing the cash flow of a period can determine if profits or losses are being generated. Therefore, it is vitally important to know the behavior of the cash flow to reduce the risk of presenting future cash deficits. Method: Se A bibliographic review was carried out identifying characteristics and variables that intervene in the cash flow of a common organization. In addition, a model is proposed that allows representing the behavior of cash flow in organizations using the variables found in the bibliographic review and which is developed using system dynamics. Results: A model was developed that is developed through system dynamics in which the cash flow variables are integrated, and in turn, allows the creation of simulation scenarios in which the cash flow variables are modified and the behavior of the flow is determined cash on time. Conclusions: With the correct parameterization of variables, using real figures and statements, it is possible to use the proposed model as an experimentation platform to evaluate the impact of implementing different policies aimed at maintaining the level of cash flow and evaluating its viability.